Synergistic effects of hybrid nanoparticles along with conventional fuel on engine performance, combustion, and environmental characteristics - Agbulut, Uemit; Saridemir, Suat (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
In this experimental work, two different nanoparticle types (Al2O3 and bN) and their binary hybrid forms (Al2O3bN) were mixed along with conventional diesel fuel (D) at 500 ppm by mass using the ultrasonication process. The tests were also carried out with completely diesel fuel (D), and reference data were collected. A singlecylinder CI engine was used for the tests at a fixed speed of 2400 rpm and variable engine loads of 3, 6, 9, and 12 Nm. In the results, BSFC value totally exhibited a decline of 8.20 % for Al2O3, 8.48 % for bN, and 9.72 % for Al2O3-bN test fuels, and BTE value totally raised by 4.21 % for Al2O3, 5.03 % for bN, and 6.64 % for Al2O3-bN test fuels as compared to the reference (D) fuel. Shortening of combustion duration, superior heat conduction capabilities, large surface/volume ratio, and improved engine performance triggered lower exhaust gas temperature (EGT) and lower NOx emissions for nanoparticle-added test fuels. NOx emission was reduced by 4.56 %, 24.57 %, and 25.85 % for Al2O3, bN, and Al2O3-bN test fuel, respectively. In addition, significant reductions in incomplete combustion pollutants such as CO and HC were also detected in the tailpipe. Numerically, CO emission was reduced by 18.75 %, 15.62 %, and 21.87 % for Al2O3, bN, and Al2O3-bN test fuel, respectively, and HC emission reduced by 4.41 %, 3.68 %, and 9.56 % for Al2O3, bN, and Al2O3-bN test fuel, respectively. In conclusion, considering all the results together, the use of nanoparticles with diesel fuel offers very promising outputs in terms of both energy efficiency and environmental aspects; however, it is possible to say that the hybrid nanoparticle usage has provided better combustion, performance, and emission results according to the mono nanoparticle usage.
Keywords: Nanofuels; Hybrid nanofuels; Combustion; Engine efficiency; Tailpipe emissions; ZINC-OXIDE; EMISSION CHARACTERISTICS; MAHUA BIODIESEL; BLENDS; Thermodynamics; Energy & Fuels